PENEMPATAN ATASE PERTAHANAN INDONESIA DI FIJI DALAM MEMPERKUAT STRATEGI DIPLOMASI PERTAHANAN DI KAWASAN PASIFIK SELATAN - Constantya Astrid Permata Sari; Makarim Wibisono; Tahan Samuel L. Toruan (Jurnal Inovasi Penelitian, 2022)
There are several challenges emerging from the South Pacific Region. Raising support related to the issue of separatism in West Papua is the challenge that most threatens national defense and Indonesia's national interest, namely maintaining territorial integrity and the establishment of the Unitary State of the Republic of Indonesia. Various diplomatic efforts, including defense diplomacy, have been carried out by Indonesia with countries in the South Pacific Region to strengthen relations and eliminate misperceptions which will eventually lead to mutual trust. This qualitative research method aims to explain how the placement of the Indonesian Defense Attaché in Fiji at the end of 2018 can strengthen Indonesia's defense diplomacy strategy in the South Pacific Region. The placement of a Defense Attache is a form of activity in defense diplomacy. Through the existence of defense attaches, it is easier for Indonesia to gather information, conduct dialogue, promotion, and negotiation in the defense sector with these countries.